Multi-residue analysis of free and conjugated hormones and endocrine disruptors in rat testis by QuEChERS-based extraction and LC-MS/MS - Pouech, Charlène; Tournier, Mikaël; Quignot, Nadia; Kiss, Agnèta; Wiest, Laure; Lafay, Florent; Flament-Waton, Marie-Magdeleine; Lemazurier, Emmanuel; Cren-Olivé, Cécile (Analytical and Bioanalytical Chemistry, 2012)
International audience Endocrine disrupting compounds (EDCs) are suspected to be responsible for many disorders of the human reproductive system. To establish a causality relationship between exposure to endocrine disruptors and disease, experiments on animals must be performed with improved or new analytical tools. Therefore, a simple, rapid, and effective multi-residue method was developed for the determination of four steroid hormones (i.e., testosterone, androstenedione, estrone, and estradiol), glucuronide and sulfate conjugates of estrone and estradiol and four endocrine disruptors in rat testis (i.e., bisphenol A, atrazine, and active metabolites of methoxychlor and vinclozolin). The sample preparation procedure was based on the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) approach. An analytical method was then developed to quantify these compounds at ultra-trace levels by liquid chromatography coupled to tandem mass spectrometry. The QuEChERS extraction was optimized with regard to the acetonitrile/water ratio used in the extraction step, the choice of the cleanup method and the acetonitrile/hexane ratio used in the cleanup step. The optimized extraction method exhibited recoveries between 89% and 108% for all tested compounds except the conjugates (31% to 58%). The detection limits of all compounds were below 20 ng g(-1) of wet weight of testis. The method was subsequently applied to determine the levels of hormones and EDCs in seven rat testis samples.